Effect of post-pressing times on adaptation of maxillary heat cured acrylic denture base at posterior palatal seal area - Firas A Farhan (College of Dentistry/ University of Baghdad, 2014)
Background: The purpose of this study was to verify the influence of post- pressing time of acrylic resin (immediate, 6, 12 and 24 hour) on the dimensional accuracy of denture base whish is a critical factor in the retention and stability of the complete denture that may occur during polymerization shrinkage. Materials and Methods: Forty maxillary stone casts were poured in plastic mold (Columbia Dentoform corp. NEW YORK, type III dental stone (Geastone, Zeus Sri Loc.Tamburine Roccastrada, GR, Italy). The stone casts were randomly assigned into 4 groups of 10 specimens each according to the post-pressing times into (immediate, 6, 12 and 24 h.). Heat cure acrylic resin denture base was constructed according to the previously mentioned pressing time, the resin base-stone cast sets were transversally sectioned with a manual saw device at the distal aspect of the molar area, anterior to the posterior palatal seal area. The gap between the resin base and stone cast was measured at five points in the right (point B) and left (point D) ridge crests, at the midline (point C), and at the right (point A) and left (point E) marginal limits (A), using a Leitz linear optical comparator microscope with a travelling stage capable of measuring 0.001 mm. Each measurement was repeated three times and the average was used as the linear gap distance for that point. The data were submitted to ANOVA. Result: there was statistically significant difference between the pressing time in which the mean values of gap space in point E for 24h shows lowest value then point A, point B, and point D than the other post pressing time. The mean value in point C shows highest values which mean the greater gap space in palatal area.